Water in the coal mining industry : an assessment of water management issues facing the coal mining industry of the Witbank and Middelburg Dam catchments - Van Rooy, J.L. (Jan Louis) (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2007.